Klotho, fibroblast growth factor‐23, and the renin–angiotensin system — an analysis from the PEACE trial. (18th February 2019) - Bergmark, Brian A.; Udell, Jacob A.; Morrow, David A.; Jarolim, Petr; Kuder, Julia F.; Solomon, Scott D.; Pfeffer, Marc A.; Braunwald, Eugene; Sabatine, Marc S.
Abstract : Aims: Klotho, an essential co‐receptor for fibroblast growth factor (FGF)‐23, has potentially beneficial inhibitory effects on the renin–angiotensin system. Limited data exist on the prognostic value of Klotho and FGF‐23 levels in combination or their ability to predict benefit from angiotensin‐converting enzyme (ACE) inhibition. Methods and results: A total of 3555 patients with stable ischaemic heart disease and left ventricular ejection fraction > 40% enrolled in the PEACE trial of trandolapril vs. placebo had Klotho levels drawn at randomization. Patients were characterized by quartiles of Klotho and FGF‐23 concentrations. Six‐year Kaplan–Meier rates and adjusted risk were calculated in the placebo arm for the composite of cardiovascular (CV) death or hospitalization for heart failure and its components. Low [quartile (Q) 1–3] Klotho concentration was associated with an increased rate of CV death or hospitalization for heart failure as compared with Q4 (8.2% vs. 4.2%; P = 0.03). After multivariable adjustment for clinical variables and renal and CV biomarkers (estimated glomerular filtration rate, cystatin‐C, urine albumin‐to‐creatinine ratio, FGF‐23, high‐sensitivity troponin T, N‐terminal pro‐B‐type natriuretic peptide, and high‐sensitivity C‐reactive protein), low Klotho concentration remained strongly associated with increased risk of CV death or hospitalization for heart failure [adjusted hazard ratio (HR) 2.62; 95% confidence interval (CI) 1.35–5.08; P < 0.01]. The combination of low Klotho and high (Q4) FGF‐23 concentration identified patients at particularly elevated risk (adjusted HR 3.99; 95% CI 1.67–9.56; P < 0.01). This high‐risk combination additionally predicted benefit from trandolapril (HR 0.39; 95% CI 0.23–0.68; P interaction < 0.01). Conclusions: Low Klotho concentration is associated with an increased risk of CV death or heart failure hospitalization in patients with stable ischaemic heart disease. The combination of low Klotho and high FGF‐23 further identifies patients at distinctly elevated risk who derive clinical benefit from the ACE‐inhibitor trandolapril.